COFFEE DRINKING HABITS WITH HYPERTENSION - Nurpratiwi; Alfikri, Fauzan; Akbar, Ali (Sean Institute, 2022)
Blood pressure is described as the ratio of systolic pressure to diastolic pressure, with its normal values ranging from 100/60 to 140/90. For the risk of blood pressure, both men and women have the possibility of developing hypertension. The habits of people who consume coffee will impact increasing blood pressure. The frequency of drinking coffee over 3 cups per day can affect blood pressure, although fact, only because of this habit that a person has an increase in blood pressure. This study aims to determine the relationship between coffee drinking habits and increased blood pressure in the community. This type of research uses an analytical description research method with a cross-sectional design of e population of the community around Pontianak city the habit of drinking coffee. The samples in this study were 50 people with a sampling technique using Probability sampling, namely with the Stratified Random Sampling technique. Data collection for coffee drinking habits using questionnaire sheets and observation sheets using a sphygmomanometer. Data analysis used Person Chi-Square and obtained p-value = 0.312 (p>0.05%). These results showed that there was between coffee drinking habits and an increase in blood pressure. Researchers advise health workers to provide health promotion about coffee drinking rules and coffee drinking doses that are good for health.